Trajetória social, de vida e escolar de idosos do MOVA no município de Embu das Artes - Carvalho, Veneranda Rocha de (2017)
This research aimed to investigate the reasons why subjects of at least 60 years of age enter the Adult Literacy Movement (MOVA), a public policy currently known as the Brazil Literacy Program (PBA), in Embu das Artes/SP. It was motivated by the high rate of illiteracy that is evident in our country and in the world. According to UNESCO's 11th Global Education Monitoring Report, there are 774 million people worldwide who can not read or write, which means that approximately 11% of the world's population is illiterate. Another motivating factor was the fact that this was the only public policy action carried out by the federal government in regards to the literacy of people over 15 years of age and developed the Brazil Literacy Program, promoted by the Secretariat for Continuing Education, Literacy, Diversity and Inclusion (SECADI) since 2003. The city of Embu das Artes/SP was chosen due to the fact that the PBA has existed there since that date, when the program was implemented nationally. Furthermore, of the 39 municipalities that make up the metropolitan area of São Paulo, only Embu das Arts has had unbroken adhesion to the program since its inception. The aim is to investigate the evolution of the social and life trajectories of subjects aged 60 and over, who were not taught to read at the appropriate age, and the reasons for and the meaning of late literacy. It was hypothesized that the reasons for returning to school are not closely linked to the relationship between the subject and reading and writing but to personal reasons. Research procedures included a questionnaire and semi-structured interviews. The authors Bourdieu (1998), Lahire (2008) and Charlot (2000) were utilized in order to comprehend the data through the concepts of cultural and social capital, identity, family configurations and relationship to knowledge, respectively. At the end of the research the hypothesis was confirmed, concluding that the senior citizens seek out schooling due to dispositions that are much more geared towards health and personal motivations, aimed at socialization rather than a desire to learn to read and write which were shown to be secondary motivations